1999
DOI: 10.1210/jcem.84.1.5412
|View full text |Cite
|
Sign up to set email alerts
|

Oral Progestogen Combined with Testosterone as a Potential Male Contraceptive: Additive Effects between Desogestrel and Testosterone Enanthate in Suppression of Spermatogenesis, Pituitary-Testicular Axis, and Lipid Metabolism1

Abstract: The effects of a synthetic oral progestogen, desogestrel (DSG), administered with low dose testosterone (T) were investigated to determine the optimal combination for suppression of gonadotropins and spermatogenesis to targets compatible with effective male contraception. Twenty-four healthy male volunteers (33.2 +/- 0.9 yr) were randomly assigned to 3 groups (n = 8) to receive: 1) 300 microg DSG orally daily and 100 mg T enanthate, i.m., weekly; 2) 300 microg DSG and 50 mg T enanthate; or 3) 150 microg DSG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Some weight gain was reported in both groups and a significant fall in HDL-C occurred in the Caucasian group but not in the Chinese subjects [50]. Weight gain has been reported in a previous similar study [19], but not in another [47]. These two studies reported a similar degree of spermatogenic suppression, with 150µg desogestrel daily and 100mg T enanthate im weekly, proving the most effective dosage combination in the former, and 300µg desogestrel and 50mg T enanthate inducing azoospermia in 8 out of 8 subjects in the latter.…”
Section: Oralmentioning
confidence: 56%
See 2 more Smart Citations
“…Some weight gain was reported in both groups and a significant fall in HDL-C occurred in the Caucasian group but not in the Chinese subjects [50]. Weight gain has been reported in a previous similar study [19], but not in another [47]. These two studies reported a similar degree of spermatogenic suppression, with 150µg desogestrel daily and 100mg T enanthate im weekly, proving the most effective dosage combination in the former, and 300µg desogestrel and 50mg T enanthate inducing azoospermia in 8 out of 8 subjects in the latter.…”
Section: Oralmentioning
confidence: 56%
“…When administered alone in men it suppressed LH, FSH and testosterone levels within 3 days, reaching a nadir at 14 days [47]. The degree of suppression achieved was greater with 300µg than with 150µg [47] but was not improved upon by the administration of a higher dose of 450µg daily [48]. A short-term dose finding study in which subjects received a single dose of 300mg of testosterone in combination with 75µg, 150µg or 300µg of desogestrel daily for 8 weeks (10 subjects per group) found that gonadotrophins fell rapidly in all groups, some men becoming azoospermic particularly in the 300µg group despite the short duration of the study [49].…”
Section: Oralmentioning
confidence: 96%
See 1 more Smart Citation
“…sadece testosteron yama ile çalışmıştır. 17,31,32 Yama ile çalışan Büchter ve ark.nın çalışmalarında ise tek bir testosteron yamanın yanı sıra oral levonorgestrel (250, 500 µg/gün) ya da oral desogestrel (300 µg/gün) kombinasyonu kullanılmıştır. 30 Bu çalışmalar istenilen sonucu vermeyince Hair ve ark.…”
Section: Erkek Kontrasepsi̇yonunda Hormonal Yöntemlerunclassified
“…15 TU ve TE'nin kas kaybı, kolesterol düzeylerinde değişim, kilo artışı, sivilce, libidoda azalma, prostat bezi, kas yoğunluğunda azalma, psikolojik değişimlere yol açması, yöntemlerin geri dönüşlerinin sağlanamaması, transdermal testosteron patch'lerin dermatite neden olması, yönteme ilişkin yapılan çalışma sonuçlarının başarısız olması, oral, intramusküler (İM) enjeksiyonlar, implantlar, flasterler, jellerin çoğunda etkinliğin başlaması için en az 1-1,5 ay sürenin geçmesi, geri dönüşleri için ise en az 3,5-5 ay süreye ihtiyaç duyulması testosteron ile birlikte progesteron ve GnRH analoğunun günlük enjeksiyon uygulanması nedeni ile gönüllülerin çalışmadan ayrılması ve uygulanma güçlüğü yeni kontrasepsiyon çalışmalarının sürdürülmesini engellemektedir. 1,22,27,[30][31][32][33][34]…”
Section: Erkek Kontrasepsi̇yon çAlişmalarinin Sürdürülmesi̇ndeki̇ Engellerunclassified